High-Altitude CO2 Clouds on Mars: OMEGA and HRSC Observations - Määttänen, Anni; Montmessin, Franck; Gondet, Brigitte; Hoffmann, Harald; Scholten, Frank; Hauber, Ernst; Gonzalez-Galindo, Francisco; Forget, François; Bibring, J.-P.; Bertaux, J.-L.; Neukum, Gerhard (2009)
The Martian climate hosts a rare phenomenon of condensation of the bulk atmosphere. CO2 condenses on the polar ice caps, but also forms clouds in the atmosphere. The existence of low-level, convective CO2 clouds in the polar night was indirectly discovered by MOLA and modeled in some studies. Recently several satellite instruments have observed CO2 clouds also near the equator, but at high altitudes where the temperatures are low enough for CO2 condensation. Montmessin et al. identified spectroscopically from MEx/OMEGA observations these high-altitude clouds to be composed of CO2 ice crystals by modeling the CO2 ice spectral signature that was observed in a deep CO2 gas absorption band at around 4.3 μm. In this work we have used the OMEGA and HRSC observations to map the occurrences of the high-altitude CO2 clouds and their properties. We have also compared the observations to the predictions of the LMD Mars Global Climate Model (LMD-MGCM) and in particular its improved version that extends to the upper atmosphere.